2011
DOI: 10.1111/j.1574-6968.2010.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and molecular clock inferences of cyanobacterial strains within Rivulariaceae from distant environments

Abstract: Heterocyst-forming cyanobacteria are important players at both evolutionary and ecological scales, but to date it has been difficult to establish their phylogenetic affiliations. We present data from a phylogenetic and molecular clock analysis of heterocystous cyanobacteria within the family Rivulariaceae, including the genera Calothrix, Rivularia, Gloeotrichia and Tolypothrix. The strains were isolated from distant geographic regions including fresh and brackish water bodies, microbial mats from beach rock, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…m3-13 from B. megaterium (Fig. 4), and with the age obtained for filamentous cyanobacteria from the same site (Domínguez-Escobar et al, 2011). This implies the presence of very ancient photosynthetic bacteria that survived all the geological changes around the site.…”
Section: Molecular Datingsupporting
confidence: 70%
“…m3-13 from B. megaterium (Fig. 4), and with the age obtained for filamentous cyanobacteria from the same site (Domínguez-Escobar et al, 2011). This implies the presence of very ancient photosynthetic bacteria that survived all the geological changes around the site.…”
Section: Molecular Datingsupporting
confidence: 70%
“…However, a prior report has suggested that the sequence EU009149 was incorrectly identified, and pertains to Calothrix , which is in good agreement with the analysis presented here. 35 The Calothrix strains that fell outside of the Calothrix clade were most likely misidentified as Calothrix , probably as a result of a morphology based identification.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work at CCB reported filamentous cyanobacteria as often the most abundant organisms within microbial mats and microbialites observed in the system (Domínguez‐Escobar et al. , Bonilla‐Rosso et al. ).…”
mentioning
confidence: 92%